Environmental transmission of generalized anxiety disorder from parents to children: worries, experiential avoidance, and intolerance of uncertainty. Issue 2 (30th June 2017) - Aktar, Evin; Nikolić, Milica; Bögels, Susan M.
Abstract : Generalized anxiety disorder (GAD) runs in families. Building on recent theoretical approaches, this review focuses on potential environmental pathways for parent-to-child transmission of GAD. First, we address child acquisition of a generalized pattern of fearful/anxious and avoidant responding to potential threat from parents via verbal information and via modeling. Next, we address how parenting behaviors may contribute to maintenance of fearful/anxious and avoidant reactions in children. Finally, we consider intergenerational transmission of worries as a way of coping with experiential avoidance of strong negative emotions and with intolerance of uncertainty. We conclude that parents with GAD may bias their children's processing of potential threats in the environment by conveying the message that the world is not safe, that uncertainty is intolerable, that strong emotions should be avoided, and that worry helps to cope with uncertainty, thereby transmitting cognitive styles that characterize GAD. Our review highlights the need for research on specific pathways for parent-to-child transmission of GAD.